A study on the rolling contact fatigue mechanism of ZC-L cast wheel steel. (June 2023) - Zhang, Guanzhen; Liu, Chunpeng; Wu, Si; Cong, Tao; Wu, Yi; Zhang, Bin; Ren, Ruiming
Highlights: A subsurface white etching microstructure (WEM) is found in wheel materials. The relationship between subsurface WEM and fatigue cracks is discussed. The relationship between subsurface casting defects and fatigue cracks is discussed. Abstract: In this paper, the rolling contact fatigue (RCF) failure mechanism of ZC-L cast steel wheels was analyzed by optical microscope (OM), scanning electron microscope (SEM) and transmission electron microscope (TEM). The results show that obvious fatigue flaking is formed on the macroscopic surface of the wheel tread after RCF failure. The RCF cracks are formed at the maximum shear stress region of the sun-surface of the wheel (1–5 mm below the tread). There are a lot of subsurface white etching microstructure (WEM) and obvious casting defects in the subsurface of the wheel tread. The RCF cracks are mainly formed at the interface between the subsurface WEM and the matrix and at the edge of the casting defects. The subsurface WEM is composed of nano-ferrite grains and residual cementite, and its hardness is about 920HV, which is much higher than that of the matrix structure. During the wear process, the plastic deformation of the subsurface WEM and the matrix is not coordinated, resulting in the formation of RCF cracks. As a hard phase, the hardness of casting defects is much higher than that of matrix. In the process of wear, under the action of subsurface stress, the casting defects can cause obvious plastic deformation in the soft orientation region at the edge of the casting defects. When the plastic deformation reaches the plastic limit, the RCF cracks are formed at the edge of the inclusions due to ratchet failure. The stress at the crack tip is caused by the RCF crack propagation at the edge of inclusions will further lead to the refinement of the microstructure at the edge of the RCF crack. Under the action of the subsurface contact stress, the subsurface WEM and casting defects are the main reasons leading to the RCF failure of the ZC-L casting wheel. Improving the microstructure uniformity and reducing casting defects are the main methods to improve the fatigue property of casting wheels.